Programa Bolsa Família - limites e possibilidades para a geração de trabalho e renda entre os beneficiários - Dalt, Salete da (2013)
This thesis aims at identifying the limits and possibilities of integrating the beneficiaries of Bolsa Família Program in labor market and income activities. Therefore, we analyzed data obtained in a national survey made by DataUFF (Núcleo de Pesquisas Sociais Aplicadas da Universidade Federal Fluminense) on this matter. The survey was conducted in two stages and its design assured comparability of data over a period of two years between each phase. The first stage runned in 2008 and the second in 2010. Data collection in 2008 was quantitatively through the homes through a structured questionnaire answered by the program's beneficiaries. Were also conducted deep interviews with beneficiaries and local implementing agents. In 2010 only the home-based questionnaries was done. We seek through the analysis of these data to verify the extent to which you can integrate the beneficiaries of Bolsa Família in the labor market or income activities and therefore the range of sustained consumption forms, which could mean the range of possibilities for financial independence regarding the state income transfer. At the end of the analysis was possible to conclude that beneficiaries suffer deficiencies in multidimensional aspects that impact on their lives and prevent proper conditions to face competition in the labor market. The main obstacles to integration into labor market were related to low education and health problems that often they referred to a depression caused by his own psychic resignation in facing the fact of not being productive and competitive. At this matter, as the generation of employment and income through incorporating into professional qualifications courses major breakthroughs has not been identified. Other strategic actions are needed to empower these families to the point of no longer need to receive money from the program and ensure its survival and of their dependents.